PTU-238 Prep, no prep or more prep? a prospective randomised study comparing two bowel preparation regimes with no preparation on quality of capsule endoscopy. (28th May 2012) - Maqboul, N; Murugananthan, A; Hong, T; French, J; Chen, R
Abstract : Introduction: Capsule endoscopy (CE) is a widely used method for evaluation of the small bowel. However it does have limitations; visualisation of the small bowel mucosa is often impaired due to the presence of food residue, air bubbles and bile pigments. 1 The effect of bowel preparation on improving visualisation of the small bowel varies 2 and is inconvenient for patients. 3 We aimed to prospectively evaluate the effects of two different bowel preparations on visualisation of the small bowel and on overall diagnostic yield compared with standard dietary changes. Methods: 51 patients (26 male/25 female; mean age 60.7 years) were randomised into three groups using the sealed envelope technique. Indications for CE were iron deficiency anaemia, obscure GI bleeding (occult and overt) and anaemia. Group 1 (n=19): Clear fluid day before procedure. Overnight fast. Group 2 (n=12): Clear fluid day before procedure. 2L PEG in afternoon of day prior to procedure. Overnight fast. Group 3 (n=20): Clear fluid day before procedure. 1L PEG and 1 sachet Picoprep in afternoon of day prior to procedure. Overnight fast. CE were viewed by a single blinded examiner and adequacy of bowel preparation according to three categories (>80% visualisation; 50%–80% visualisation). Results: Conclusion: Our findings are in keeping with a recent meta-analysis which has shown no difference in CE completion rates, GTT and SBTT with purgative preparation. 4 Our study shows a trend towards better caecal completion rates with bowel preparation involving PEG and Picoprep, but these results did not reach statistical significance. Overall diagnostic yield was similar in all three groups. Liquid diet, in combination with fasting, prior to CE is generally better tolerated by patients 3 and our findings would support this as adequate preparation for CE. Mean age Completion rate (%) Yield (%) Good SB views (%) Mean GTT ± SEM (min) Mean SBTT ± SEM (min) Gp 1 63.6 79 42.1 100 35.9±11.19 254.8±24.83 Gp 2 57 83.3 41.6 81.2 87.5±47.79 239.3±45.7 Gp 3 60 90 35 79 74.8±27.06 211.5±24.14 p Value NS NS NS NS Competing interests: None declared. References: 1. Park SC, Keum B, Seo YS, et al. Effect of bowel preparation with polyethylene glycol on quality of capsule endoscopy. Dig Dis Sci 2011;56 :1769–75. 2. Dai N, Gubler C, Hengstler P, et al. Improved capsule endoscopy after bowel preparation. Gastrointest Endosc 2005;61 :28–35. 3. Pons Beltrán V, González Suárez B, González Asanza C, et al. Evaluation of different bowel preparations for small bowel capsule endoscopy: a prospective, randomised, controlled study. Dig Dis Sci 2011;56 :2900–5. 4. Rokkas T, Papaxoinis K, Triantafyllou K, et al. Does purgative preparation influence the diagnostic yield of small bowel video capsule endoscopy? : a meta-analysis. Am J Gastroenterol 2009;104 :219–27.